The Optimization of Website Visibility and Traffic by Implementing Search Engine Optimization (SEO) in Palembang Polytechnic of Tourism - Setiawan, Agus; Harahap, Zulkifli; Syamsuar, Dedy; Kunang, Yesi Novaria (Bina Nusantara University, 2020)
This research is a case study of Search Engine Optimization (SEO) in Palembang Polytechnic of Tourism website. The main objective of this research is to establish a plan for SEO in Palembang Polytechnic of Tourism (http://poltekpar-palembang.ac.id/) and to improve online visibility and ranking position in search engines (Google). It aims to bring in more international traffic and students to visit the website. SEO is a digital marketing technique to increase web accessibility. In the globalization world, people use search engines, such as Google, to know or find out more about various topics quickly and visually. Through a bibliographic review and qualitative analysis, the research focuses on the understanding of what SEO is and its implementation for the Palembang Polytechnic of Tourism website. The results show that the most important thing in making SEO plans is to increase visibility and branding on search engines (Google). SEO is done by developing website content and setting keywords as backlinks.